ANTIMICROBIAL SENSITIVITY OF BACTERIAL FLORA ASSOCIATED WITH SEPTICAEMIC VIBRIOSIS IN TIGER SHRIMP, PENAEUS MONODON - MISHRA, S. S.; DHIMAN, M.; DAS, PRIYANKA; MALI, P.; DAS, M. K. (Journal of the Inland Fisheries Society of India, 2022)
Among the groups of microorganisms affecting shrimp culture, vibrios are the best known bacteria responsible for devastating economic losses both in shrimp hatchery and culture farms (Lavilla-Pitogo, 1995). Various Vibrio spp. have been implicated in major mortality cases in juvenile penaeid shrimp(Karunasagar et al., 1994) and involved as primary pathogens in shell disease (Lightner, 1996). Vibrio parahaemolyticus and V. alginolyticus have been isolated from cases of septicaemic vibriosis, black spot and shellnecrosis disease in shrimp (Sinderman and Lightner, 1988). Vibrio spp. are regarded as members of the normal bacterial flora of shrimp, often acting as opportunistic pathogens under stressful conditions inflicting mortalities up to 100% (Lightner, 1996). However, other Vibrio spp., Aeromonas spp. and Flavobacterium spp. have been isolated and shown to be involved in diseaseconditions of shrimp (Lavilla-Pitogo, 1995; Sinderman and Lightner, 1988). Again V. parahaemolyticus, a common inhabitant of brackishwater and coastal marine water has been of great public health significance (Josephet al., 1982), warranting methods for their diagnosis and control. Another aspect, which demands urgent attention is development and transmission of drug resistant strains of bacteria in aquatic ecosystem. The regular andcontinuous use of antibiotics in shrimp and fish culture has been associated with increased incidence of antibiotic resistant bacteria (Abraham et al., 1997; Karunasagar et al., 1994; Mohney et al., 1994). The role ofantimicrobial compounds in controlling infectious diseases in cultured fish and shellfish has been well recognized. A wide range of aqua-drugs are being marketed and used in aquaculture. Detailed comparativestudies of different aqua-drugs to assess their anti-bacterial potential and suitability for aquaculture applications are essential (Hameed and Rao, 1994). This communication reports the sensitivity of selected bacteria isolated from diseased shrimp, Penaeus monodon to antibiotics and commercially available aqua-drugs, commonly used in fish and shrimpculture.